(untitled) (LIS TODAY, 2024)
Recent past year, there has been renewed interest in research evaluations and it play vital role for building reputations of country, organization, institutes and also individual researcher. Several studies have documented on research evaluation using bibliometric cc indicator. In this paper, applied bibliometrics indicator for evaluate the research preference of Sociology research published in India between 1991 and 2020. We accessed Scopus database and retrieved 2410 publications. The growth of both citations and publications was not stable overtime period fluctuated. Result showed that, Indian Sociologist scholarly communion communicated in various format and preferable source of journal was “Economic and Political Weekly”. More than half of the publications communicated individually rather than collaboratively. Jawaharlal Nehru University and University of Delhi standout in top leading organization in terms of contributions. Top most frequently keyword was “India”. Indian sociologist prefers to collaborate with developing countries such as USA and UK.